(untitled) (Scientific journal of the Fergana State University, 2024)
The article provides information on the chemical composition and healing properties of pumpkin seeds. The norms of daily consumption of pumpkin seeds and how much of the necessary substances can be replenished for the body from this are presented. data is given on the chemical composition of pumpkin, its healing properties, the norm of human daily life and how many percent it satisfies its daily needs. Products from natural medicinal plants of origin not only retain their relevance, but are increasingly becoming objects of research of scientists from different countries of the world. Such natural sources include pumpkin. during our study, the results of the total amount of flavonoids, β-carotenoids in the product Tark were presented, as well as antioxidant activity through phytochemical tests. Pumpkin seeds are useful, from which it is recommended to prepare a food additive. Pumpkin has its rich chemical composition, which is becoming objects of research in a number of scientific centers around the world. This trend is characterized naturally, on the one hand, by the historically proven effectiveness of their use and, on the other hand, by the fact that it